Nomenclatural notes on Heliocarya (Boraginaceae) from Iran - Ranjbar, Massoud; Khalvati, Sina (Phytotaxa, 2020)
The new combination of Heliocarya actinobole (Bunge) Ranjbar & Khalvati is proposed for the species widely known as Caccinia actinobole and a lectotype for it is designated.